2021
DOI: 10.3946/kjme.2021.189
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on happiness and stress: comparison of preclinical and clinical medical students

Abstract: Purpose To compare differences in happiness and stress and related factors between pre-clinical and clinical year medical students during the coronavirus disease 2019 (COVID-19) pandemic. Methods A cross-sectional study was conducted in the Faculty of Medicine, Chiang Mai University, Thailand. All undergraduate medical students were requested to voluntarily respond to an electronic survey. Demographic data, related factors of happiness and stress, scores from the Thai v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The Oxford Happiness Questionnaire (OHQ) was used in an online study of 369 preclinical and clinical medical students in China (2021); no difference was observed between the groups regarding happiness and stress. Factors related to a higher degree of happiness were satisfaction with health and a physical exercise program [47]. This result reinforces the importance of physical exercise for controlling many symptoms, such as those related to anxiety and depression, which contributes to improving happiness.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The Oxford Happiness Questionnaire (OHQ) was used in an online study of 369 preclinical and clinical medical students in China (2021); no difference was observed between the groups regarding happiness and stress. Factors related to a higher degree of happiness were satisfaction with health and a physical exercise program [47]. This result reinforces the importance of physical exercise for controlling many symptoms, such as those related to anxiety and depression, which contributes to improving happiness.…”
Section: Discussionsupporting
confidence: 66%
“…Spielberger's State-Trait Anxiety Inventory [20] is a self-administered questionnaire composed of two scales with 20 items of up to 4 points each, where one scale evaluates the state and the other evaluates the trait of anxiety; the higher the score is, the worse the level of anxiety [21,22]. Some authors classi ed the level of anxiety as low (< 33), medium (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) or high (> 49), which is the classi cation that we used in this study [23,24].…”
Section: Anxiety Assessment -Spielberger State-trait Anxiety Inventor...mentioning
confidence: 99%
“…In this study, we used single-item measures of happiness and PI. This decision is based on previous studies that measured medical student’s SH [ 13 , 24 , 49 ] and medical students’ and science, technology, engineering, and mathematics (STEM) students’ PI [ 33 , 50 ], and showed that SH and PI can be validly and reliably evaluated via single-item measurement. Additionally, in order to increase the response rate, a single-item measure for SH and PI is used [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested in another study that the overall sense of well-being may be assessed quickly and efficiently through a brief measure of happiness [ 23 ]. Additionally, measuring happiness using a single item is reliable, valid, and viable [ 24 ]. In order to measure pre-medical students’ perceptions of the importance of PI (Professional identity) after they entered medical school, we used the following item: “Future Physician (Prospective Doctor) is one of the main aspects of my identity and I consider its importance is...?” The level of importance ranges from “1 = not at all” to “6 = a great deal.” In order to reduce the size and complexity of the questionnaire for participants and improve the response rate [ 32 ], we used this measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation